The influence of regulator on television content in post-authoritarian Indonesia - Morissan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Throughout the authoritarian era, the government imposed tight control on television content in Indonesia. However, after the fall of the last authoritarian ruler in 1998, and the old style of restriction no longer exist, the question now remains: who ultimately control television content? This research measures the influence of political and economic factors on television content with a focus on owners, advertisers, audiences, regulators, and politicians. A questionnaire survey was conducted on 400 television workers employed at 10 national private television stations in Indonesia. Qualitative data was produced from the interview with 50 television workers with a focus on the role of the regulator in influencing content. Key research questions are: 1) what are the most influential politics and economic factors that influence television workers in shaping the content? 2) How does the regulator influence television workers in shaping the content? The findings showed that the audience is the most influential factor since it affected 33.9 percent of television workers. The regulator appeared to be the least influence on programmes content on a daily basis. This showed that the influence of regulators experienced a drastic decline from the strongest in the authoritarian era to the weakest in the post-authoritarian era. However, the influence of regulators was still quite significant among television workers who worked at TV stations and relied heavily on entertainment programmes.